Removal of the Most Probable Number of coli from Hospital Wastewater Using Nanofiltration Membranes - Ian Kurniawan (Science Journal Get Press, 2025)
Hospitals are significant sources of wastewater containing pathogenic microorganisms, particularly enteropathogenic and toxigenic Escherichia coli (E. coli), which pose serious health and environmental risks if left untreated. This study evaluated the effectiveness of nanofiltration (NF) membranes in reducing E. coli concentrations in hospital wastewater using the Most Probable Number (MPN) method. Samples were collected from a type B hospital in Palembang, Indonesia, and treated with NF membranes operated at 60 psi and contact times between 10 and 60 seconds.The NF membrane achieved high removal efficiencies ranging from 99.75% to 100%, with complete elimination of E. coli at retention times of 30 seconds or more. This confirms nanofiltration as an effective tertiary treatment method for improving the microbiological quality of hospital effluent and ensuring compliance with discharge standards. The membrane's performance is attributed to its fine pore size and electrostatic repulsion of bacterial cells.To enhance practical application, future studies should focus on scaling up to full or industrial levels, evaluating long-term performance, fouling behavior, maintenance needs, and economic feasibility. Such efforts are vital to integrating nanofiltration into sustainable hospital wastewater management systems that protect public and environmental health.